Morpho-physiological responses of sweet basil, Ocimum basilicum L., to non-aerated hydropolic culture - De Guzman, Constancio C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
Sweet basil, Ocimum basilicum L., was grown under a simple, non-aerated hydroponic culture system developed by the Asian Vegetable Research and Development Center (AVDRC) in Taiwan. Plants grown in partial or complete submersion of roots in non-aerated Hoagland's nutrient solution (HS) were compared with those in a corresponding fully aerated HS medium as control; other plants were grown in a commercial fertilizer solution (CFS). Plant growth parameters, except for root length and number of adventitious roots, were not significantly affected by the treatments. Roots were longest when only the lower roots were partially in contact with the aerated HS, while the greatest number of adventitious roots was observed in non-aerated HS. There were no significant differences in the level of N, P, K and Mg in the different organs of sweet basil with root submersion and aeration treatments. submerged in aerated HS. Calcium content of the leaves was highest when the entire root was completely submerged in aerated HS. Mean daily rate of transpiration was highest for plants that were partially in contact with an aerated HS. In general, under the AVRDC system, growth of sweet basil was significantly better when grown in a non-aerated nutrient medium using HS than with a CFS as nutrient medium.